ANALISIS TRADE-OFF INFLASI DAN PERTUMBUHAN EKONOMI KALIMANTAN TIMUR - Junaidi, Agus (FORUM EKONOMI, 2016)
According to Phillip’s Curve, a rising in growth or reduction in employment rate will cause rise in inflation rate. In economics this phenomenon was named growth inflation trade-off. This study examines whether in East Kalimantan appeared growth inflation trade-off. By using multiple linear regression analysis was found that there isn’t growth inflation trade-off phenomenon in East Kalimantan.Keyword: Growth, inflation, growth inflation trade-off.